Implementation and improvement of Integrated Management Systems: recommendations for their adaptation to the ISO High-Level structure - Fernanda Ellen Francisco; Ana Carolina Ferreira Costa; Paulo Alexandre Costa Araújo Sampaio; Pedro Domingues; Otávio José de Oliveira (Cleaner Environmental Systems)
In the face of the high competitiveness in the marketplace, many companies have sought ways to differentiate themselves from others by improving the quality of their products and services, reducing the environmental impact, and ensuring employee safety. In this context, many companies implemented some management systems such as ISO 9001 (Quality Management), ISO 14001 (Environmental Management), and ISO 45001 (Occupational Health and Safety Management) to improve their performance. The International Organization for Standardization (ISO) created in 2012 a high-level structure (Annex SL) that serves as the basis for the development and integration of these Certifiable Management systems (CMSs), making them more compatible and effective. However, many companies do not have sufficient expertise about the latest versions of ISO 9001 and ISO 14001 and about the publication of ISO 45001 based on the structure proposed by Annex SL, bringing difficulties for their Integrated Management Systems (IMS). The objective of this work is to propose recommendations that direct companies to adapt their IMSs to the modifications arising from Annex SL. To develop this study, four case studies were made in Brazilian industrial companies with the following data collection instruments (semi-structured interviews, on-site observation, and document analysis). Our case studies were carried out in large companies because these types of organizations generally have more than two management systems implemented, and our article focuses on systems integration. In addition, these companies develop several interesting solutions that can serve as benchmarking for small and medium-sized companies. With this study it was possible to develop guidelines related to greater emphasis on the analysis of the organizational context; the importance of promoting a culture of integration; the need for leadership responsible for the integration of CMSs, etc. The main scientific contribution of this work was to deepen and update the theory about certifiable management systems and IMS according to the results obtained from empirical studies. The main applied contribution of this study is to generate a competitive advantage for the company over its competitors by providing leaders with management solutions that make it possible to implement or improve IMS based on the modifications resulting from Annex SL.